Evaluating the Performance of Transport Protocols over MMP - Delgado Martín, Ana Victoria; Mihailovic, Andrej; Georganopoulos, Nikos; Aghvami, A. H. (My University, 2000)
TCP is a reliable connection-oriented transport protocol that performs well in traditional networks. However, in networks with wireless and other lossy links the protocol suffers from losses and delays due to frequent handoffs like in wireless networks running Mobile IP. Many Micromobility Protocols have been proposed to reduce handoff latency and the load on the network when we move among small wireless cells. In this paper, the performance of several TCP and UDP schemes over one of these protocols: MMP (Multicast for Mobility Protocol) is compared and different improvements to TCP in a multiple handoff network are proposed. The simulation results are presented using the Network Simulator (ns2) and different metrics for comparison. Our results show that the number of UDP packets lost is reduced when using MMP instead of Mobile IP and that TCP provides better throughput performance for a traditional scheme like Tahoe TCP.